Eish - when to use -ish-: a study in the verbalization of English lexical items in spoken Xhosa - Madubela, Ndumiso S (School of Languages and Literatures, 2021)
This study examines how Xhosa speakers incorporate verbs of English origin into their lexicons with a specific focus on the -ish- suffix. The study deals with historical treatments of this phenomenon and debates its relevance and applicability to current scholarship on lexical borrowing. To ensure a wide range of data sources I used a corpus derived from interviews with 30 Xhosa speakers in Cape Town, as well as from three media sources: the first is a 1-hour long talk radio programme transcribed from the national Xhosa broadcaster, UMhlobo weNene, the second an interview with a Xhosa-speaking patient on the television programme, Siyayinqoba Beat It. The third is from social media, (Facebook, Twitter and WhatsApp). The demographics of participants in this study are predominantly urban dwellers. The youngest participant (from the surveys) was 16 years old and the oldest participant was 45 years old. I say “predominantly” as it was not possible to obtain specific background data to the two Xhosa speakers on radio and television. Very little work has been done on the way in which African languages speakers grammaticalize verbs of English origin – why, for example, do some adopted words like suffix -a (e.g. Ndiyamotivate-a – ‘I am motivating') while others suffix -ish-a (e.g. Ndiyastudy-ish-a – ‘I am studying'). The main finding of the study is that speakers incorporated verbs of English origin by suffixing -a and -ish- in their speech, they were not consciously code mixing: rather, they used these suffixes as just another resource available to them to make their communication more strategic. This could indicate that in certain urban settings the -ish- verbalizing suffix might become even more popular as people need to negotiate lifestyles that require new lexicons. It is hoped that this research will shed more light on this growing phenomenon and provide a framework for discussion of verbalizers within the greater canon of language change scholarship in South Africa as a whole. A primary function of this study was to formulate rules for the adoption of -ish- and -a and to provide statistical data as to which one is preferred by speakers.